Enhancing Innovative Work Behavior Through High-Involvement HRM Practices and Knowledge Management Capability - Mar’atus Sholikah; Anni Safitri; Kusuma Wijaya; Kresna Rahma Aji (Fakultas Ekonomi Universitas Garut, 2026)
High-Involvement Human Resource Management (HI-HRM) has been recognized as an important driver of employee innovation; however, the mechanism through which it influences Innovative Work Behavior (IWB) remains underexplored. This study examines the mediating role of Knowledge Management Capability (KMC) in the relationship between HI-HRM and IWB among workers in the MSME and industrial sectors in Jepara Regency, Indonesia. This study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (SEM-PLS). Data were collected from 132 workers in the MSME and industrial sectors through purposive sampling. The structural model demonstrated substantial explanatory power, with R² values of 0.734 for IWB and 0.600 for KMC. The results indicate that HI-HRM has a significant positive effect on KMC (β = 0.775; p < 0.001) and IWB (β = 0.455; p < 0.001). KMC also has a significant positive effect on IWB (β = 0.454; p < 0.001). Furthermore, KMC partially mediates the relationship between HI-HRM and IWB (β = 0.352; p < 0.001), highlighting the importance of knowledge management capability in translating HRM practices into innovative employee behavior. These findings support the Resource-Based View (RBV) and Dynamic Capability Theory by demonstrating that KMC functions as a strategic capability linking human resource management practices and innovation outcomes. The study suggests that organizations should strengthen knowledge management systems and implement high-involvement HRM practices to enhance sustainable innovation and competitiveness.